SUSTAINABLE MINING TOWARDS ACCOMPLISHING CIRCULAR ECONOMY PRINCIPLES - Petronijevic, Nela; Alivojvodić, Vesna; Sokić, Miroslav; Marković, Branislav; Stanković, Srđan; Radovanović, Dragana (Journal of Applied Engineering Science, 2020)
Today human society is already witnessing rapid depletion of non-renewable ore resources. As the distribution of raw material resources globally is very off-balance, and preassure on environment as the consequence of ore exploatation is not negligible, re-utilization and recycling of industrial side-streams gaining on importance. Finding new potentially anthropogenic resources of material (at first place critical raw materials) are inline with sustainable waste management goals, and in correlation with boundaries given by the circular economy principles. Side-streams from mines can become source for recovery of these materials. The aim of this paper was to analyze position of mining waste in correlation with circular economy principles, as well potential for implementation of them within extraction industry in the Republic of Serbia.
Keywords: mine waste; raw materials; circular economy